Sensor-triggered sampling to determine instantaneous airborne vapor exposure concentrations. - Smith, Philip A.; Simmons, Michael K.; Toone, Phillip (Journal of Occupational & Environmental Hygiene, 2018)
It is difficult to measure transient airborne exposure peaks by means of integrated sampling for organic chemical vapors, even with very short-duration sampling. Selection of an appropriate time to measure an exposure peak through integrated sampling is problematic, and short-duration time-weighted average (TWA) values obtained with integrated sampling are not likely to accurately determine actual peak concentrations attained when concentrations fluctuate rapidly. Laboratory analysis for integrated exposure samples is preferred from a certainty standpoint over results derived in the field from a sensor, as a sensor user typically must overcome specificity issues and a number of potential interfering factors to obtain similarly reliable data. However, sensors are currently needed to measure intra-exposure period concentration variations (i.e., exposure peaks). In this article, the digitized signal from a photoionization detector (PID) sensor triggered collection of whole-air samples when toluene or trichloroethylene vapors attained pre-determined levels in a laboratory atmosphere generation system. Analysis by gas chromatography-mass spectrometry of whole-air samples (with both 37 and 80% relative humidity) collected using the triggering mechanism with rapidly increasing vapor concentrations showed good agreement with the triggering set point values. Whole-air samples (80% relative humidity) in canisters demonstrated acceptable 17-day storage recoveries, and acceptable precision and bias were obtained. The ability to determine exceedance of a ceiling or peak exposure standard by laboratory analysis of an instantaneously collected sample, and to simultaneously provide a calibration point to verify the correct operation of a sensor was demonstrated. This latter detail may increase the confidence in reliability of sensor data obtained across an entire exposure period.